LEVEL OF IMPLEMENTATION OF INTERNATIONAL FUNDING OF AGRICULTURAL DEVELOPMENT-VALUE CHAIN DEVELOPMENT PROGRAMME IN TARABA STATE, NIGERIA - J. J, YIDAU; A. A. , TAFIDA; I. D, YUSUF (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The review examined the level of implementation of international funding of agricultural development-value chain development programme in Taraba State, Nigeria, such as been neither widely acknowledged nor explicitly credited. Speicically the paper evaluates the level of implementation of IFAD-VCDP and the constraints experienced by the programme in Taraba State. The review identified achievements of IFAD-VCDP such as Agricultural market development, smallholder productivity enhancement and permanent temporary jobs for both adult and youths. The Programme trained youths at various institutions on entrepreneurship; development on operation and maintenance of road and infrastructure facilities, use of smart tractor, seed multiplication on rice and cassava stem, spraying techniques to form sprayer group mention but a few. The constraints identified were branding and packaging of products; agricultural marketing Information system, Value chain aggregators established to facilitate sustainability not effectively serving their members and access to machinery enterprise is limited. It is therefore recommended that capacity of the beneficiaries of branding should be further enhanced through appropriate trainings and education should be targeted.